BGP desing and implementation - Zhang, Randy (Cisco Press, 2004)
With guidelines for designing and deploying a scalable Border Gateway Protocol (BGP) routing architecture, this book examines the challenges for the service provider and enterprise customers. It offers examples, case studies, and implementation procedures. BGP improvements and features incorporated into Cisco IOS Software are covered.